Corporate Carbon Footprint of a Palm Oil Mill - Moreno García, José Edwin; Martínez, Leonel Alexander; Belalcázar Cerón, Luis Carlos; Rojas, Nestor Yecid (TECCIENCIA, 2018)
Colombia is the largest producer of palm oil in America. An estimate of the carbon footprint of a Colombian agro-industrial company during 2011 is presented in this paper. Only the operations conducted within the company’s processing plant are considered. Greenhouse gas emissions are estimated by applying the methodology proposed by the Intergovernmental Panel on Climate Change (IPCC), which considers the physical chemical properties and emission factors for fuels and activities described by the Colombian Mining and Energy Planning Unit. The carbon footprint is found to be 115,352 t CO2 for the studied year. Of these emissions, 58% correspond to anaerobic open lagoons for water treatment, 41% to stationary combustion equipment, and only 1% to transportation vehicles and heavy machinery owned by the company. By identifying emission sources and estimating the carbon footprint, this company is now able to set objectives leading to a reduction in emissions and the implementation of strategies to minimize environmental effects caused by this process.